1977
DOI: 10.1128/aac.11.5.871
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Resistance to d -Cycloserine in Bacillus subtilis 168

Abstract: Resistance to D-cycloserine could be induced in Bacillus subtilis 168 by sublethal concentrations of D-cycloserine. Sensitivity to the antibiotic could be regained by growth in the absence of D-cycloserine. The bactericidal activity of )-cycloserine apparently was not altered by resistant cells, and peptidoglycan synthesis was still inhibited by D-cycloserine in resistant cells. The n-cycloserine resistance apparently resulted from a decreased uptake of the antibiotic. The decrease in n-cycloserine transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…2B). The novel D-cycloserine resistance protein had low-level identity to a drug/metabolite transporter (46% identity over 91% of the sequence; YP_001583420), indicating the gene may have efflux-related function, consistent with known mechanisms of D-cycloserine tolerance (22). …”
mentioning
confidence: 92%
“…2B). The novel D-cycloserine resistance protein had low-level identity to a drug/metabolite transporter (46% identity over 91% of the sequence; YP_001583420), indicating the gene may have efflux-related function, consistent with known mechanisms of D-cycloserine tolerance (22). …”
mentioning
confidence: 92%
“…DCS has been documented as being either bacteriostatic or bactericidal depending upon the concentration and the susceptibility of a particular bacterium (Curtiss et al . ; Clark and Young ). Additionally, Clark and Young demonstrated that early logarithmic stage cells of Bacillus subtilis were highly sensitive to DCS, whereas during late stage growth, the authors were more likely to observe resistance to DCS.…”
Section: Discussionmentioning
confidence: 98%
“…The new parameters may be evaluated by the use of long-term experiments, but these have the disadvantage that the culture might either become 'trained' to a certain concentration of cycloserine (Clark & Young, 1977) or even that resistant mutants may arise.…”
Section: Discussionmentioning
confidence: 99%
“…A similar competition has been observed for the uptake system by which the amino acids D-alanine and glycine, as well as the antibiotic cycloserine, are transported into the cell (Wargel et al, 1970). The resistance of E. coli (Wargel et al, 1971), Bacillus subtilis (Clark & Young, 1977) and Rhizobium sp. (Pankhurst & Craig, 1979) to cycloserine has been shown to be coupled with variations in this uptake system.…”
Section: Introductionmentioning
confidence: 99%